Effect of structure forming additives on the of water bond forms in gluten-free macaroni dough made from corn flour - Rozhno, Oleksandr; Yurchak, Vera; Holikova, Tatiana (My University, 2017)
The water bond forms in dough for gluten-free macaroni products made from corn fine meal flour with addition of different structure forming additives - xanthan, carboximethylcellulose (CMC), gelatin and dry egg white - have been investigated. Research shows that speed of drying of macaroni products made from corn flour with xanthan, gelatin and dry egg white (till first critical moisture (W1 cr)) is higher that contribute to apply harder drying regimes in first period. W1 cr for corn macaroni samples is 28.70-23.40 % that is less than in the wheat products.
Keywords: gluten-free products; forms of water bonds; structure forming additives; speed of drying; безглютенові вироби; форми зв’язку води; структуроутворювачі; швидкість сушіння; кафедра готельно-ресторанної справи; кафедра технології хлібопекарських і кондитерських виробів